Prevalence of smoking habit and its variations in patients reporting to a private dental institution: a retrospective study - DAVE, PAVITHRA H; MAHESWARI, T.N.UMA; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2021)
The prevalence of tobacco use has increased over the past decades. Traditional forms like betel quid, tobacco with lime and tobacco tooth powder are commonly used, and the use of new products is increasing, not only among men but also among children, teenagers and women. The aim of the study is to find the prevalence of smoking habits and its variations in patients reporting to a private Dental University, India. The case sheets of patients were obtained from the patient record system. The data of each patient regarding the duration, type and pattern of smoking habit was obtained and tabulated. The results of the study show prevalence of the pattern of smoking habit in conventional smoking is 69% and in reverse smoking is 31%. Prevalence of type of smoking tobacco showed prevalence of cigarettes to be 96% and to be bidi 4%. The present study shows there is a significant association based on comparison of age with pattern of smoking and age with the duration of smoking done using chi square test (p value-0.000). Thus higher prevalence was seen in the age group of 41-60 years (48%), 21-40 years (42%) and in males with cigarettes being the most preferred smoking tobacco. As cigarettes are accessible, it is also more carcinogenic and it is increasing among the youth, hence precautions must be taken in earlier age groups of 21-40 years for early interventions such as anti tobacco sessions and guidance to decrease the consumption of tobacco.